1964
DOI: 10.1083/jcb.23.3.447
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Organization Of, and the Relationship Between the Organic Matrix and the Inorganic Crystals of Embryonic Bovine Enamel

Abstract: Electron microscope and electron diffraction studies of developing embryonic bovine enamel have revealed the organization of the organic matrix and the inorganic crystals. The most recently deposited inorganic crystals located at the ameloblast-enamel junction are thin plates, approximately 1300 A long, 400 A wide, and 19 A thick. During maturation of the enamel, crystal growth occurs primarily by an increase in crystal thickness. Statistical analyses failed to show a significant change in either the width or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(91 citation statements)
references
References 47 publications
(85 reference statements)
3
88
0
Order By: Relevance
“…22 If the presence of peroxide in the prismatic spaces is the explanation for the adverse influence on adhesion, the effect on bovine enamel would not be similar to the effect on human enamel due to the inherent differences in structure and size of the interprismatic areas. 21 However, while bovine teeth do not lead to results that are identical with those obtained from human teeth, they produce results that are comparable and certainly useful in evaluating the influence of various treatments on enamel bond strengths. 9 Bovine enamel was used in the current study, both because large numbers of human enamel specimens were difficult to obtain and the current study determined the efficient time periods for the application of an antioxidant gel.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…22 If the presence of peroxide in the prismatic spaces is the explanation for the adverse influence on adhesion, the effect on bovine enamel would not be similar to the effect on human enamel due to the inherent differences in structure and size of the interprismatic areas. 21 However, while bovine teeth do not lead to results that are identical with those obtained from human teeth, they produce results that are comparable and certainly useful in evaluating the influence of various treatments on enamel bond strengths. 9 Bovine enamel was used in the current study, both because large numbers of human enamel specimens were difficult to obtain and the current study determined the efficient time periods for the application of an antioxidant gel.…”
Section: Discussionmentioning
confidence: 96%
“…Although there are differences in density and porosity of human and bovine enamel, 21 the mechanism of acid etching is similar. 22 If the presence of peroxide in the prismatic spaces is the explanation for the adverse influence on adhesion, the effect on bovine enamel would not be similar to the effect on human enamel due to the inherent differences in structure and size of the interprismatic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of developing enamel and its insoluble portion of the organic matrix has been extensively analyzed, and evidence of aligned fibrillar protein structures has been provided by electron microscopy (Perdok and Gustafson, 1961;Travis and Glimcher, 1964;Nanci et al, 1985). In addition, x-ray diffraction (XRD) studies on fixed and demineralized enamel matrices were performed to investigate the presence of secondary structures of the enamel proteins.…”
mentioning
confidence: 99%
“…These analyses were one of the difficult studies for hard tissues, but it is now easy by using the IP-micro-XRD technique. Travis and Glimcher 21) reported the developing bovine enamel crystals by transmission electron microscope, TEM, and electron diffraction, ED. They observed that during maturation of the enamel, crystal growth occurred primarily by an increase in crystal thickness and crystals within the enamel prisms were oriented parallel to the long axes of the prisms.…”
Section: Discussionmentioning
confidence: 99%